Composite material, light emitting diode and display device

CN114665030BActive Publication Date: 2026-10-27TCL TECHNOLOGY GROUP CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011549128.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2026-10-27
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

[0004]本申请的目的在于提供一种复合材料,以及一种含有该复合材料的发光二极管及其制备方法,旨在解决现有的电子传输材料的电子传输效率较高,难以与空穴传输材料匹配,导致量子点发光层带电,加速器件老化,降低器件寿命的问题

Benefits of technology

[0012]本申请提供的复合材料,物质储存材料中含有可以反应生成碳酸的气体CO2。物质储存材料可以缓慢释放CO2,并反应生成碳酸,生成的碳酸进一步与电子传输材料反应形成金属碳酸盐,可以降低电子传输材料的电子注入效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114665030B_ABST
    Figure CN114665030B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of display, and provides a composite material, a light emitting diode and a display device. The composite material comprises an electron transport material and a substance storage material containing an active substance, wherein the electron transport material contains a metal element, the substance storage material has a porous structure, the active substance at least comprises CO2, and the metal element can form a metal carbonate with CO2. The composite material provided by the application contains the gaseous CO2 which can react to generate carbonic acid. The substance storage material can slowly release CO2 and react to generate carbonic acid, and the generated carbonic acid further reacts with the electron transport material to form a metal carbonate, so that the electron injection efficiency of the electron transport material can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of display technology, and in particular relates to composite materials and light-emitting diodes. Background Technology

[0002] With the continuous innovation and development of science and technology, contemporary people have increasingly higher demands for displays with larger screens, higher resolutions, lower power consumption, and thinner designs. Quantum dot light-emitting diodes (QLEDs), as a novel thin-film light-emitting display device, have received widespread attention from the scientific research and industrial communities in recent years. Compared with existing OLED (Organic light-emitting diode) technology, QLEDs exhibit significant advantages, primarily in terms of low cost, long lifespan, low power consumption, high color gamut, high electro-optical conversion efficiency, and suitability for large screens, making them a promising candidate for next-generation flat panel displays.

[0003] With the continuous optimization and development of quantum dot materials and the structure and functional layers of QLED devices, the performance of QLEDs has made significant progress. The efficiency of red, green, and blue devices can basically meet the needs of commercial applications. The real bottleneck restricting their market application lies in the device's lifetime. Due to the significant difference in the transport rates of the hole and electron transport layers on the anode and cathode sides, charge carriers cannot effectively recombine in the quantum dot emitting layer, causing the quantum dot emitting layer to become charged, accelerating device aging, and reducing device lifetime. Therefore, how to balance the effective recombination of charge carriers in QLED devices and reduce non-radiative recombination, thereby improving device lifetime, is a crucial problem that urgently needs to be solved for commercialization. Summary of the Invention

[0004] The purpose of this application is to provide a composite material, a light-emitting diode containing the composite material, and a method for preparing the same, in order to solve the problem that existing electron transport materials have high electron transport efficiency, making it difficult to match with hole transport materials, which leads to the quantum dot light-emitting layer being charged, accelerating device aging, and reducing device lifespan.

[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:

[0006] The first aspect of this application provides a composite material comprising an electron transport material and a substance storage material containing an active substance, wherein the electron transport material contains a metal element, the substance storage material has a porous structure, the active substance comprises at least CO2, and the metal element is capable of forming a metal carbonate with CO2.

[0007] A second aspect of this application provides a light-emitting diode, including an electron transport layer. The electron transport layer is made of an electron transport material, a matter storage material, and a metal carbonate. The electron transport material contains a metal element, and the matter storage material has a porous structure. The metal carbonate is obtained by reacting an active substance contained in the matter storage material with the electron transport material, and the active substance includes at least CO2 gas.

[0008] A third aspect of this application provides a method for fabricating a light-emitting diode, comprising the following steps:

[0009] An electron transport prefabrication layer is prepared by forming a hybrid material of electron transport material and material storage material on a device substrate. The electron transport material contains a metal element, and the material storage material has a porous structure that contains a gas, the gas of which includes at least CO2.

[0010] The remaining layers constituting the light-emitting diode are fabricated on the electron transport prefabrication layer to obtain the prefabricated light-emitting diode;

[0011] The pre-fabricated light-emitting diode is subjected to vacuum and / or heating conditions to obtain a light-emitting diode.

[0012] The composite material provided in this application contains CO2 gas, which can react to form carbonic acid, in the material storage material. The material storage material can slowly release CO2 and react to form carbonic acid. The generated carbonic acid further reacts with the electron transport material to form metal carbonates, which can reduce the electron injection efficiency of the electron transport material.

[0013] The light-emitting diode provided in this application contains a metal carbonate in its electron transport layer, formed by the reaction of an active material carried by a matter storage material with the electron transport material. This metal carbonate reduces the electron injection efficiency of the electron transport material, addressing the problem of carrier imbalance in the light-emitting layer caused by the significant difference in the transport rates of holes and electrons. Specifically, during the reaction between the active material carried by the matter storage material and the electron transport material, the active material is uniformly released through the matter storage material, resulting in a uniform presence of the formed metal carbonate in the electron transport layer, thereby more effectively improving the device's lifespan.

[0014] The method for fabricating a light-emitting diode provided in this application involves uniformly releasing the gas stored in the material storage material in the electron transport prefabrication layer under vacuum and / or heating conditions, so that the gas and gaseous reactants can react uniformly with the electron transport material, thereby generating uniformly distributed metal carbonates in the electron transport layer. The uniformly distributed metal carbonates can increase the difficulty of electron injection into the electron transport material, thereby reducing the electron injection efficiency of the electron transport layer and improving the lifespan of the device.

[0015] A fourth aspect of this application provides a display device that includes any of the aforementioned light-emitting diodes. The display device may be a device with a display screen, such as a mobile phone, computer, or television. Attached Figure Description

[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a schematic diagram of the structure of the light-emitting diode provided in the embodiments of this application;

[0018] Figure 2 This is a schematic diagram of the structure of a positive light-emitting diode provided in an embodiment of this application;

[0019] Figure 3 This is a schematic diagram of the structure of the inverted light-emitting diode provided in the embodiments of this application;

[0020] Figure 4 This is a fabrication process diagram of the light-emitting diode provided in the embodiments of this application. Detailed Implementation

[0021] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0022] In the description of this application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0023] In a first aspect, embodiments of this application provide a composite material, including an electron transport material and a matter storage material, wherein the electron transport material contains a metal element, the matter storage material has a porous structure, and the porous structure contains a gas, the gas including at least CO2.

[0024] The composite material provided in this application embodiment contains CO2 gas, which can react to generate carbonic acid, in the material storage material. The material storage material can slowly release CO2 and react to generate carbonic acid. The generated carbonic acid further reacts with the electron transport material to form metal carbonates, which can reduce the electron injection efficiency of the electron transport material.

[0025] In this embodiment, the composite material contains an electron transport material, which serves as the main functional material, promoting electron injection and transport to impart electron injection and transport performance to the composite material. The electron transport material contains a metal element, which acts as a reactant element, reacting with carbonic acid (a reactant in the gas mixture stored in the material storage material) or carbonic acid (a reactant between the gas and other active ingredients) to generate a metal carbonate. The metal carbonate reduces the electron injection efficiency of the electron transport material, thereby imparting a suitable electron injection efficiency to the composite material. This matches the hole injection efficiency of the hole transport material in the light-emitting diode, better balancing electron and hole injection in the device and thus improving device performance.

[0026] In one possible implementation, the electron transport material is selected from at least one of doped or undoped metal compounds and non-metal compounds doped with metal elements. The metal in the metal compound and the doped metal can both serve as reacting elements in the metal carbonate.

[0027] In some embodiments, in the non-metallic compound doped with metal elements and the doped metallic compound, the doping element is independently selected from at least one of Al, Mg, In, Li, Ga, Cd, Cs, and Cu. Metal carbonates formed by Al, Mg, In, Li, Ga, Cd, Cs, and Cu with carbonic acid can all reduce electron injection into the electron transport layer.

[0028] In some embodiments, the electron transport material is selected from at least one of doped or undoped metal oxides, doped or undoped semiconductor materials, and nitrides. Exemplarily, the metal oxide is selected from at least one of titanium dioxide (TiO2), zinc oxide (ZnO), zirconium oxide (ZrO), tin oxide (SnO2), tungsten oxide (WO3), tantalum oxide (Ta2O3), hafnium oxide (HfO3), aluminum oxide (Al2O3), zirconium silicon oxide (ZrSiO4), barium titanium oxide (BaTiO3), and barium zirconium oxide (BaZrO3). Exemplarily, the semiconductor material is selected from at least one of CdS, ZnSe, and ZnS. Exemplarily, the nitride is selected from Si3N4, but is not limited thereto.

[0029] The composite material provided in this application embodiment contains, in addition to an electron transport material, a matter storage material. The matter storage material has a porous structure and is used to contain and store gas. Specifically, the gas is stored within the porous structure of the matter storage material.

[0030] In some embodiments, the content ratio of electron transport material to matter storage material in the composite material is 0.01 to 0.5:1. If the content of matter storage material is low, the amount of gas adsorbed is too small, resulting in the generation of a small amount of zinc carbonate in the electron transport material, which is insufficient to block electron transport and thus fails to improve device performance. If the content of matter storage material is too high, the amount of gas adsorbed is too large, resulting in the generation of excessive zinc carbonate in the electron transport material, causing excessive electron blocking. When the composite material is used as an electron transport layer material, electrons cannot be effectively injected into the light-emitting layer, such as a quantum dot light-emitting layer, thereby reducing device performance.

[0031] In some embodiments, the material storage material is selected from at least one of metal-organic frameworks (MOFs) and covalent organic frameworks (COFs). MOFs are porous materials with a repeating network structure formed by the self-assembly of metal ions and organic ligands. They possess large porosity and specific surface area, enabling them to contain and release gases. Because the metal central ions in MOFs do not fully participate in coordination, the uncoordinated metal central ions readily combine with gases such as inorganic acids, H₂O, O₂, and CO₂ to satisfy their coordination requirements. After adsorbing a certain amount of gas, MOFs can release these molecules through heating or vacuum treatment, thereby achieving the effective release of a specified amount and type of substance. COFs are crystalline materials with an ordered porous structure, also possessing large porosity and specific surface area, enabling them to contain and release gases. Furthermore, they exhibit good adsorption performance, capable of adsorbing surrounding gases into their porous structure under heating or vacuum treatment conditions.

[0032] In some embodiments, the material stores gaseous substances. In some embodiments, the material storage material can also store non-gaseous substances. That is, the porous structure of the material storage material contains both gaseous and non-gaseous substances, wherein the non-gaseous substances can be stored in the porous structure of the material storage material either in a gaseous manner or in a non-gaseous manner.

[0033] In one possible implementation, the storage material contains a gas mixture comprising CO2, H2O, and O2. In this case, the H2O in the gas mixture first reacts with the CO2 to produce carbonic acid; then, the carbonic acid reacts with an electron transport material to form a metal carbonate, which can impede electron injection. For example, the electron transport material is ZnO, and the generated carbonic acid reacts with ZnO to form zinc carbonate, which can significantly impede electron injection.

[0034] In some embodiments, the molar ratio of H2O contained in the material storage material to CO2 contained in the material storage material is 0.8 to 2:1. If the H2O content is too low, a small amount of zinc carbonate will be generated in the electron transport material, which is insufficient to block electron transport, thus failing to achieve the purpose of improving device performance. If the H2O content is too high, when the composite material is used as the electron transport layer material of optoelectronic devices, excessive water can easily penetrate into the light-emitting layer, such as the quantum dot light-emitting layer, causing a decrease in the light-emitting performance of the light-emitting material, such as the quantum dot material itself, thereby affecting the device performance.

[0035] In a preferred embodiment, the molar ratio of H2O to CO2 is 1:1. In this case, H2O and CO2 in the material storage can react as completely as possible to generate carbonic acid in a molar ratio of 1:1, thereby minimizing the residual gas in the composite material.

[0036] In some embodiments, the molar ratio of H2O contained in the material storage material to that in the electron transport material in the composite material is 0.01 to 1:1. If the H2O content is too low, a small amount of zinc carbonate will be generated in the electron transport material, which is insufficient to block electron transport, thus failing to improve device performance. If the water content is too high, when the composite material is used as the electron transport layer material of an optoelectronic device, excessive water can easily penetrate into the light-emitting layer, causing a decrease in the luminescence performance of the light-emitting material, such as quantum dot materials, thereby affecting device performance.

[0037] In one possible implementation, the material storage material contains inorganic acid and CO2. In this case, the inorganic acid released from the material storage material first reacts with hydroxyl groups on the surface of the electron transport material to generate inorganic acid anion ligands and water. The inorganic acid anion ions can fill the defect states formed after the reaction of the hydroxyl groups on the electron transport material surface. The elimination of hydroxyl groups on the electron transport material surface can effectively reduce the exciton quenching problem at the interface between the light-emitting layer and the electron transport layer. Simultaneously, the generated water can react with the carbon dioxide released from the material storage material to produce carbonic acid. The carbonic acid reacts with the electron transport material to generate metal carbonates, which can hinder electron injection. For example, the electron transport material is ZnO, and the generated carbonic acid reacts with ZnO to generate zinc carbonate, which can greatly hinder electron injection.

[0038] In some embodiments, the molar ratio of inorganic acid to CO2 in the material storage is 0.8 to 2:1. When the composite material is used as the electron transport layer material of an optoelectronic device, if the inorganic acid content is too high, excessive hydrochloric acid can easily penetrate into the light-emitting layer, adversely affecting the luminescence of the light-emitting material, especially quantum dots; if the inorganic acid content is too low, it is not conducive to removing the hydroxyl groups on the surface of the electron transport material, resulting in insufficient water content, which in turn results in too little zinc carbonate generated, failing to play the role of blocking electrons and balancing charge carriers.

[0039] In a preferred embodiment, the molar ratio of inorganic acid to CO2 is 1:1. In this case, the inorganic acid in the material storage material reacts with the hydroxyl groups on the surface of the electron transport material, and the resulting inorganic acid anion has a molar ratio of 1:1 with CO2 to react as completely as possible to generate carbonic acid, thereby minimizing the residual gas in the composite material.

[0040] In some embodiments, the molar ratio of inorganic acid in the material storage material to electron transport material in the composite material is 0.01 to 1:1. When the composite material is used as the electron transport layer material of an optoelectronic device, if the inorganic acid content is too high, excessive hydrochloric acid can easily penetrate into the light-emitting layer, adversely affecting the luminescence of light-emitting materials such as quantum dots; if the inorganic acid content is too low, it is not conducive to removing the hydroxyl groups on the surface of the electron transport material, resulting in insufficient water content, which in turn results in too little zinc carbonate, failing to play its role in blocking electrons and balancing charge carriers.

[0041] For example, the inorganic acid is selected from dichromic acid (H2Cr2O7), diphosphoric acid (H4P2O7), hypoiodic acid (HIO), hypochlorous acid (HClO), hypobromic acid (HBrO), hypophosphoric acid (H3PO2), hyposulfuric acid (H2SO2), superoxide acid (HO2), iodic acid (HIO3), telluric acid (H2TeO4), fluoroboric acid (HBF4), fluorosilicic acid (H2SiF6), fluoroantimonyic acid (HSbF6), fluorophosphoric acid (HPF6), fluorosulfuric acid (HSO3F), fluoroplatinic acid (HPtF6), fluorooxynic acid (HOF), vanadic acid (HVO3), perchloric acid (HClO4), permanganic acid (HMnO4), ferric acid (H2FeO4), periodic acid (HIO4·2H2O), and high... Bromic acid (HBrO3), perxenic acid (H4XeO6), chromic acid (H2CrO4), silicic acid (H2SiO3), cobalt acid (HCoO2), peroxymonosulfuric acid (H2SO5), peroxydisulfuric acid (H2S2O8), peroxydicarbonic acid (H2C2O6), perboric acid (HBO3), percarbonic acid (H2CO4), peroxyacid (hydrogen peroxide H2O2), pyrophosphate (H4P2O7), pyrosulfuric acid (H2S2O7), metabisulfite (H2S2O5), tetrathionic acid (H2S4O6), dithionite (H2S2O4), phosphoric acid (H3PO4), phosphomolybdic acid (P2O5·24MoO3·3H2O), thiosulfate (H2S2O3), sulfuric acid (H2SO4), thiocyanate (HSCN), chloric acid (HClO3), chloroauric acid (HAuCl4), chloroplatinic acid (H2PtCl6), chlorosulfonic acid (HSO3Cl), aluminic acid (aluminum hydroxide H3AlO3), manganese acid (H2MnO4), molybdic acid (H2MoO4), nickel acid (HNiO2), boric acid (H3BO3), metaboric acid (HBO2), metaphosphoric acid (HPO3), metaarsine (HAsO2), metaaluminic acid (HAlO2), lead acid (H2PbO3), cyanic acid (HCNO), hydroiodic acid (HI), hydroazide acid (HN3), hydrotelluric acid (H2Te), hydrofluoric acid (HF), hydrosulfuric acid (H2S), hydrochloric acid [HCl], hydrocyanic acid (HCN), hydrobromic acid (HBr), arsenic acid (H3AsO4), trisilicic acid (H4Si3O8), tetraboric acid (H2B4O7), tetrahydroxyaluminic acid [HAl(OH)4], tetrahydroxycubic acid [H2Cu(OH)4], titanic acid (H2TiO4), carbonic acid (H2CO3), ferric acid (HFeO2), tungstic acid (H2WO4), nitric acid (HNO3), selenic acid (H2SeO4), stannic acid (H2SnO3), zincic acid (H2ZnO2), bromic acid (HBrO3), xenonic acid (H2XeO4), tellurite (H2TeO3), sulfurous acid (H2SO3), phosphoric acid (H3PO3), chlorite (HClO2), hydrochloric acid (HCl), chromite (HCrO2), lead oxide (H2PbO2)At least one of the following inorganic acids is used: arsenous acid (H3AsO3), nitrous acid (HNO2), selenous acid (H2SeO3), stannic acid (H2SnO2), uranic acid (H2UO4), orthosilicic acid (H4SiO4), orthophosphoric acid (H5PO5), orthosulfuric acid (H6SO6), and orthocarbonic acid (H4CO4). These inorganic acids react with the hydroxyl groups on the surface of the electron transport material to generate inorganic acid anion ligands and water. The inorganic acid anions fill the defect states formed after the reaction of the hydroxyl groups on the electron transport material surface, effectively reducing the exciton quenching problem at the interface between the luminescent layer and the electron transport layer. Simultaneously, the generated water reacts with carbon dioxide released from the material storage material to produce carbonic acid.

[0042] Secondly, embodiments of this application provide a light-emitting diode, including an electron transport layer. The electron transport layer is made of an electron transport material, a matter storage material, and a metal carbonate. The electron transport material contains a metal element, and the matter storage material has a porous structure. The metal carbonate is obtained by reacting an active substance contained in the matter storage material with the electron transport material, and the active substance includes at least CO2 gas.

[0043] The light-emitting diode provided in this application embodiment contains a metal carbonate in its electron transport layer, formed by the reaction of an active material carried by a matter storage material with the electron transport material. This metal carbonate reduces the electron injection efficiency of the electron transport material, addressing the problem of carrier imbalance in the light-emitting layer caused by the significant difference in the transport rates of holes and electrons. Specifically, during the reaction between the active material carried by the matter storage material and the electron transport material, the active material is uniformly released through the matter storage material, resulting in a uniform presence of the formed metal carbonate in the electron transport layer, thereby more effectively improving the device's lifespan.

[0044] In this embodiment, the electron transport layer contains an electron transport material, which serves as the main functional material, promoting electron injection and transport to endow the electron transport layer with electron injection and transport properties. The electron transport material contains metallic elements.

[0045] In one possible implementation, the electron transport material is selected from at least one of doped or undoped metal compounds and non-metal compounds doped with metal elements. The metal in the metal compound and the doped metal can both serve as reacting elements in the metal carbonate.

[0046] In some embodiments, in the non-metallic compound doped with metal elements and the doped metallic compound, the doping element is independently selected from at least one of Al, Mg, In, Li, Ga, Cd, Cs, and Cu. Metal carbonates formed by Al, Mg, In, Li, Ga, Cd, Cs, and Cu with carbonic acid can all reduce electron injection into the electron transport layer.

[0047] In some embodiments, the electron transport material is selected from at least one of doped or undoped metal oxides, doped or undoped semiconductor materials, and nitrides. Exemplarily, the metal oxide is selected from at least one of titanium dioxide (TiO2), zinc oxide (ZnO), zirconium oxide (ZrO), tin oxide (SnO2), tungsten oxide (WO3), tantalum oxide (Ta2O3), hafnium oxide (HfO3), aluminum oxide (Al2O3), zirconium silicon oxide (ZrSiO4), barium titanium oxide (BaTiO3), and barium zirconium oxide (BaZrO3). Exemplarily, the semiconductor material is selected from at least one of CdS, ZnSe, and ZnS. Exemplarily, the nitride is selected from Si3N4, but is not limited thereto.

[0048] In this embodiment, the electron transport layer material also contains a matter storage material with a porous structure, which provides storage space for the raw materials used to generate metal carbonates.

[0049] In some embodiments, the ratio of electron transport material to matter storage material in the electron transport layer is 0.01 to 0.5:1. If the content of matter storage material is low, the amount of adsorbed gas is too small, resulting in the formation of a small amount of zinc carbonate in the electron transport material, which is insufficient to block electron transport and thus fails to improve device performance. If the content of matter storage material is too high, the amount of adsorbed gas is too large, resulting in the formation of excessive zinc carbonate in the electron transport material, causing excessive electron blocking and preventing the effective injection of electrons into the light-emitting layer, such as the quantum dot light-emitting layer, thereby reducing device performance.

[0050] In some embodiments, the substance storage material is selected from at least one of metal-organic frameworks (MOFs) and covalent organic frameworks (COFs). MOFs can adsorb a certain amount of gas, and after heating or vacuum treatment, release these molecules, thereby achieving the effective release of a specified amount and type of substance. COFs are crystalline materials with an ordered porous structure, possessing large porosity and specific surface area, capable of containing and releasing gases. Furthermore, they exhibit good adsorption properties, able to adsorb surrounding gases into their porous structure under heating or vacuum treatment conditions.

[0051] In this embodiment, the electron transport layer material further includes metal oxides, and the metal carbonates are obtained by reacting the active material contained in the material storage material with the electron transport material. Specifically, the metal carbonates are obtained by reacting the active material contained in the material storage material with the metal in the electron transport material. The metal carbonates are used to reduce the electron injection efficiency of the electron transport material, thereby giving the composite material a suitable electron injection efficiency, which matches the hole injection efficiency of the hole transport material in the light-emitting diode, better balancing the injection of electrons and holes in the device, and thus improving the device performance.

[0052] In this embodiment of the application, the active substance contained in the material storage material includes at least CO2 gas, which serves as the carbon source for carbonic acid.

[0053] In one possible implementation, the active material is an active gaseous substance, including CO2, as well as H2O and O2. In this case, the H2O in the active gaseous substance first reacts with CO2 to produce carbonic acid; then, the carbonic acid reacts with an electron transport material to form a metal carbonate, which can hinder electron injection. For example, the electron transport material is ZnO, and the generated carbonic acid reacts with ZnO to form zinc carbonate, which can greatly hinder electron injection.

[0054] In some embodiments, the molar ratio of H2O to CO2 in the active gaseous substance is 0.8 to 2:1. If the H2O content is too low, a small amount of zinc carbonate will be generated in the electron transport material, which is insufficient to block electron transport, thus failing to achieve the purpose of improving device performance. If the H2O content is too high, excessive water can easily penetrate into the quantum dot light-emitting layer, causing a decrease in the self-luminescence performance of the quantum dot material, thereby affecting device performance.

[0055] In a preferred embodiment, the molar ratio of H2O to CO2 is 1:1. In this case, H2O and CO2 in the active gaseous substance can react as completely as possible to generate carbonic acid in a molar ratio of 1:1, thereby minimizing the residual gas in the electron transport layer.

[0056] In some embodiments, the molar ratio of H2O to electron transport material in the electron transport layer is 0.01 to 1:1. If the H2O content is too low, a small amount of zinc carbonate will be generated in the electron transport material, which is insufficient to block electron transport, thus failing to improve device performance. If the H2O content is too high, excessive water can easily penetrate into the light-emitting layer, such as the quantum dot light-emitting layer, causing a decrease in the light-emitting performance of the light-emitting material, such as the quantum dot material itself, thereby affecting device performance.

[0057] In one possible implementation, the active material includes CO2 and an inorganic acid. In this case, the inorganic acid released from the storage material first reacts with hydroxyl groups on the surface of the electron transport material to generate inorganic acid anion ligands and water. The inorganic acid anions can fill the defect states formed after the reaction of the hydroxyl groups on the electron transport material surface; simultaneously, the generated water reacts with carbon dioxide released from the storage material to produce carbonic acid. The carbonic acid reacts with the electron transport material to form a metal carbonate, which can hinder electron injection. For example, the electron transport material is ZnO; the generated carbonic acid reacts with ZnO to form zinc carbonate, which can significantly hinder electron injection.

[0058] In some embodiments, the molar ratio of inorganic acid to CO2 in the active material is 0.8 to 2:1. If the inorganic acid content is too high, excessive hydrochloric acid can easily penetrate into the light-emitting layer, adversely affecting the luminescence of the light-emitting material, especially quantum dots. If the inorganic acid content is too low, it is not conducive to removing the hydroxyl groups on the surface of the electron transport material, resulting in insufficient water content and thus insufficient zinc carbonate, which cannot play a role in blocking electrons and balancing charge carriers.

[0059] In a preferred embodiment, the molar ratio of inorganic acid to CO2 is 1:1. In this case, the inorganic acid released from the material storage material reacts with the hydroxyl groups on the surface of the electron transport material, and the resulting inorganic acid ions react with CO2 in a molar ratio of 1:1 to generate carbonic acid as completely as possible, thereby minimizing the residual gas in the composite material.

[0060] In some embodiments, the molar ratio of inorganic acid to electron transport material in the composite material is 0.01 to 1:1. If the inorganic acid content is too high, excessive hydrochloric acid can easily penetrate into the light-emitting layer, adversely affecting the luminescence of light-emitting materials such as quantum dots. If the inorganic acid content is too low, it is not conducive to removing the hydroxyl groups on the surface of the electron transport material, resulting in insufficient water content and thus insufficient zinc carbonate, which cannot play a role in blocking electrons and balancing charge carriers.

[0061] For example, the inorganic acid is selected from dichromic acid (H2Cr2O7), diphosphoric acid (H4P2O7), hypoiodic acid (HIO), hypochlorous acid (HClO), hypobromic acid (HBrO), hypophosphoric acid (H3PO2), hyposulfuric acid (H2SO2), superoxide acid (HO2), iodic acid (HIO3), telluric acid (H2TeO4), fluoroboric acid (HBF4), fluorosilicic acid (H2SiF6), fluoroantimonyic acid (HSbF6), fluorophosphoric acid (HPF6), fluorosulfuric acid (HSO3F), fluoroplatinic acid (HPtF6), fluorooxynic acid (HOF), vanadic acid (HVO3), perchloric acid (HClO4), permanganic acid (HMnO4), ferric acid (H2FeO4), periodic acid (HIO4·2H2O), and high... Bromic acid (HBrO3), perxenic acid (H4XeO6), chromic acid (H2CrO4), silicic acid (H2SiO3), cobalt acid (HCoO2), peroxymonosulfuric acid (H2SO5), peroxydisulfuric acid (H2S2O8), peroxydicarbonic acid (H2C2O6), perboric acid (HBO3), percarbonic acid (H2CO4), peroxyacid (hydrogen peroxide H2O2), pyrophosphate (H4P2O7), pyrosulfuric acid (H2S2O7), metabisulfite (H2S2O5), tetrathionic acid (H2S4O6), dithionite (H2S2O4), phosphoric acid (H3PO4), phosphomolybdic acid (P2O5·24MoO3·3H2O), thiosulfate (H2S2O3), sulfuric acid (H2SO4), thiocyanate (HSCN), chloric acid (HClO3), chloroauric acid (HAuCl4), chloroplatinic acid (H2PtCl6), chlorosulfonic acid (HSO3Cl), aluminic acid (aluminum hydroxide H3AlO3), manganese acid (H2MnO4), molybdic acid (H2MoO4), nickel acid (HNiO2), boric acid (H3BO3), metaboric acid (HBO2), metaphosphoric acid (HPO3), metaarsine (HAsO2), metaaluminic acid (HAlO2), lead acid (H2PbO3), cyanic acid (HCNO), hydroiodic acid (HI), hydroazide acid (HN3), hydrotelluric acid (H2Te), hydrofluoric acid (HF), hydrosulfuric acid (H2S), hydrochloric acid [HCl], hydrocyanic acid (HCN), hydrobromic acid (HBr), arsenic acid (H3AsO4), trisilicic acid (H4Si3O8), tetraboric acid (H2B4O7), tetrahydroxyaluminic acid [HAl(OH)4], tetrahydroxycubic acid [H2Cu(OH)4], titanic acid (H2TiO4), carbonic acid (H2CO3), ferric acid (HFeO2), tungstic acid (H2WO4), nitric acid (HNO3), selenic acid (H2SeO4), stannic acid (H2SnO3), zincic acid (H2ZnO2), bromic acid (HBrO3), xenonic acid (H2XeO4), tellurite (H2TeO3), sulfurous acid (H2SO3), phosphoric acid (H3PO3), chlorite (HClO2), hydrochloric acid (HCl), chromite (HCrO2), lead oxide (H2PbO2)At least one of the following: arsenous acid (H3AsO3), nitrous acid (HNO2), selenous acid (H2SeO3), stannic acid (H2SnO2), uranic acid (H2UO4), orthosilicic acid (H4SiO4), orthophosphoric acid (H5PO5), orthosulfuric acid (H6SO6), and orthocarbonic acid (H4CO4). These inorganic acids react with the hydroxyl groups on the surface of the electron transport material to generate inorganic acid anion ligands and water. The inorganic acid anions fill the defect states formed after the reaction of the hydroxyl groups on the electron transport material surface; the generated water can react with carbon dioxide released from the material storage to produce carbonic acid.

[0062] In some embodiments, the thickness of the electron transport layer is 10–180 nm, thereby achieving a good electron injection effect.

[0063] In some embodiments, such as Figure 1 As shown, the light-emitting diode includes a cathode 10 and an anode 60 disposed opposite to each other, and a light-emitting layer 40 disposed between the cathode 60 and the anode 10. An electron transport layer 50 is disposed between the cathode 60 and the light-emitting layer 40.

[0064] In some embodiments, the light-emitting diode further includes a hole functional layer disposed between the anode 10 and the light-emitting layer 40. The hole functional layer includes at least one of a hole transport layer, a hole injection layer, and an electron blocking layer. In some embodiments, the light-emitting diode further includes an electron injection layer disposed between the cathode 60 and the electron transport layer 50.

[0065] In the above embodiments, the light-emitting diode may further include a substrate, with the anode 10 or the cathode 60 disposed on the substrate.

[0066] The light-emitting diode provided in this application embodiment can be, for example, such as Figure 2 The positive light-emitting diode shown or such Figure 3 The inverted light-emitting diode shown.

[0067] In the above embodiments, the substrate 100 can be a rigid substrate or a flexible substrate, specifically glass, silicon wafer, polycarbonate, etc.

[0068] The anode 10 can use common anode materials and thicknesses, and in some embodiments, the anode comprises a metal or an alloy thereof. Exemplarily, the material of the anode 10 includes at least one selected from zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), and fluorine-doped tin oxide.

[0069] In some embodiments, the material of the hole injection layer 20 includes poly(ethylene dioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamines, poly(N-vinylcarbazole), etc. In some embodiments, the thickness of the hole injection layer 20 is 20-200 nm.

[0070] In some embodiments, the hole transport layer is made of an organic material, which may be selected from arylamines. Exemplary examples include 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4”-diamine (α-NPD), etc. In some embodiments, the thickness of the hole transport layer 30 is 30–180 nm.

[0071] In this embodiment, the light-emitting layer 40 can be divided into an organic light-emitting layer and a quantum dot light-emitting layer according to the type of light-emitting material. The material of the organic light-emitting layer is an organic light-emitting material, and the light-emitting material in the quantum dot light-emitting layer is a quantum dot. Correspondingly, when the light-emitting layer 40 is an organic light-emitting layer, the light-emitting diode is an organic light-emitting diode; when the light-emitting layer 40 is a quantum dot, the light-emitting diode is a quantum dot light-emitting diode. In some embodiments, the quantum dot is selected from at least one of group II-VI quantum dots such as CdS, group III-V quantum dots such as GaN, and group IV-VI quantum dots such as SnS.

[0072] In some embodiments, the thickness of the light-emitting layer 40 is 30–180 nm. In some embodiments, the light-emitting layer 40 is a quantum dot hybrid light-emitting layer, and the total thickness of the light-emitting layer is 30–180 nm.

[0073] In this embodiment, the material and thickness of the electron transport layer 50 are as described above and will not be repeated here.

[0074] In some embodiments, the cathode 60 is made of a metal or metal alloy. For example, the cathode 60 may be made of one or more of magnesium, calcium, sodium, potassium, titanium, indium, yttrium, lithium, gadolinium, aluminum, silver, tin, lead, cesium, and barium.

[0075] In some embodiments, the electron transport layer material contains O2 in the mass storage material, and the cathode material includes a metal. Specifically, the cathode contains a metal near the interface of the electron transport layer. In this case, the O2 released from the mass storage material reacts with the metal in the cathode to generate a metal oxide at the interface between the cathode and the electron transport layer. The generated oxide (such as aluminum oxide) can further hinder electron injection to some extent, which further promotes the effective recombination of charge carriers in the light-emitting layer, thereby improving the device lifetime.

[0076] In the above embodiments, the thickness of the bottom electrode (the electrode closer to the substrate) is 20-200 nm; the thickness of the top electrode (the electrode farther from the substrate) is 40-190 nm.

[0077] The light-emitting diodes provided in the embodiments of this application can be prepared by the following method.

[0078] Fourthly, such as Figure 4 As shown in the figure, this application provides a method for fabricating a light-emitting diode, including the following steps:

[0079] S01. An electron transport prefabrication layer is prepared by forming a mixture of electron transport material and matter storage material on a device substrate, wherein the electron transport material contains a metal element, the matter storage material has a porous structure, and the porous structure contains a gas, the gas including at least CO2.

[0080] In this step, the hybrid material of electron transport material and material storage material is the composite material described above. To save space, the composition of the hybrid material and its preferred configuration will not be described here.

[0081] A hybrid material of electron transport material and matter storage material is formed on a device substrate. In the resulting electron transport prefabrication layer, a predetermined active material is quantitatively adsorbed by the matter storage material and mixed with the electron transport material to form a hybrid material layer. The device substrate can be determined according to either a normal or inverted device structure. In some embodiments, the device substrate is a cathode substrate; in other embodiments, the device substrate includes at least an anode substrate and a light-emitting layer, and further, a hole functional layer may be present between the anode substrate and the light-emitting layer.

[0082] In some embodiments, the preparation method of the mixed material is as follows: after placing a predetermined molar amount of a gas mixture in a sealable container, a material storage material is placed in the mixture, allowing the material storage material to adsorb the gas mixture. In this case, a fixed amount of a specific target gas (such as CO2, H2O and O2, or CO2 and inorganic acid) can be adsorbed into the material storage material, thereby achieving uniform doping of carbonates in the electron transport material.

[0083] In some embodiments, after the material storage material is placed in the mixture, the temperature of the sealable container is controlled at 18–40°C and the pressure at 0.001 MPa–10 MPa to promote the adsorption of gas by the material storage material.

[0084] S02. The remaining layers constituting the light-emitting diode are prepared on the electron transport prefabrication layer to obtain the prefabricated light-emitting diode.

[0085] Based on the composition of the device substrate described in the above steps, the remaining layers constituting the light-emitting diode are fabricated on the electron transport prefabrication layer. In some embodiments, the device substrate is a cathode substrate, and fabricating the remaining layers constituting the light-emitting diode on the electron transport prefabrication layer includes: fabricating a light-emitting layer on the electron transport prefabrication layer, fabricating a cathode on the light-emitting layer, and further, before fabricating the cathode, fabricating a hole-functional layer on the light-emitting layer. In some embodiments, the device substrate is a substrate comprising at least an anode substrate and a light-emitting layer, and further, a hole-functional layer may be present between the anode substrate and the light-emitting layer. In this case, fabricating the remaining layers constituting the light-emitting diode on the electron transport prefabrication layer includes: fabricating a cathode on the electron transport prefabrication layer. Further, before fabricating the cathode on the electron transport prefabrication layer, fabricating an electron injection layer on the electron transport prefabrication layer.

[0086] In some embodiments, this step further includes encapsulating the pre-fabricated light-emitting diode. In some embodiments, an electronic encapsulating adhesive is used to encapsulate the pre-fabricated light-emitting diode.

[0087] S03. The pre-fabricated light-emitting diode is subjected to vacuum and / or heating conditions to obtain a light-emitting diode.

[0088] In this step, the active substances stored in the material storage material are uniformly released in a gaseous state or by other methods through vacuum and / or heating treatment, reacting with the electron transport material to form metal carbonates. In some embodiments, the material storage material stores gases such as H2O, O2, and CO2, which are uniformly released in this step. H2O reacts with CO2 to generate carbonic acid, which further reacts with the electron transport material to form metal carbonates; O2 reacts with the metal in the cathode to form metal oxides. In some embodiments, the material storage material stores inorganic acids and CO2. The inorganic acid can be stored in a gaseous state or in a non-gaseous state, such as a solid state, and is uniformly released in this step. The inorganic acid reacts with the surface hydroxyl groups of the electron transport material to generate inorganic acid anions, which can fill the defect states formed after the hydroxyl groups on the surface of the electron transport material; simultaneously, the generated water reacts with the carbon dioxide released from the material storage material to produce carbonic acid. The carbonic acid further reacts with the electron transport material to form metal carbonates.

[0089] In this step, because the gas or non-gaseous substances in the material storage are released uniformly, the generated zinc carbonate is uniform across the entire film layer, which provides an important guarantee for the long lifespan of the device.

[0090] In some embodiments, the vacuum level is less than 0.1 MPa, the heating temperature is 40°C to 180°C, and the heating time is 1 min to 48 h. In this case, heating or pressurizing can promote the release of gaseous or non-gaseous substances from the material storage material.

[0091] The method for fabricating a light-emitting diode provided in this application involves uniformly releasing gas stored in a material storage material from an electron transport prefabrication layer under vacuum and / or heating conditions. This allows the gas and gaseous reactants to react uniformly with the electron transport material, thereby generating a uniformly distributed metal carbonate in the electron transport layer. The uniformly distributed metal carbonate increases the difficulty of electron injection into the electron transport material, thus reducing the electron injection efficiency of the electron transport layer and improving the device's lifespan. Furthermore, this method is very simple, effective, and controllable, providing a solid foundation for the subsequent fabrication of high-performance devices.

[0092] The following description is based on specific embodiments.

[0093] Example 1:

[0094] A quantum dot light-emitting diode, the fabrication method of which includes:

[0095] An anode is fabricated on a substrate, a hole injection layer is fabricated on the anode, a hole transport layer is fabricated on the hole injection layer, a quantum dot emitting layer is fabricated on the hole transport layer, an electron transport layer is fabricated on the quantum dot emitting layer, and a cathode is fabricated on the electron transport layer. After the device fabrication is completed, the device is heat-treated at 120°C for 60 min. The substrate is a glass substrate; the bottom electrode is ITO with a thickness of 80 nm; the hole injection layer is PEDOT:PSS with a thickness of 40 nm; the hole transport layer is TFB with a thickness of 100 nm; the quantum dot emitting layer is CdZnSe / ZnSe / ZnS, each with a thickness of 80 nm; the electron transport layer is a mixed layer of ZnO and MOF materials, in which the MOF material is SIFSIX-3-Ni, and gases such as H2O, O2, and CO2 are adsorbed in the following proportions. The molar ratio of H2O to CO2 is 1:1, the molar ratio of H2O to electron transport material ZnO is 0.02:1, the molar ratio of O2 to the cathode is 0.03:1, and the thickness of the electron transport layer is 50 nm; the top electrode is Al with a thickness of 50 nm.

[0096] Comparative Example 1

[0097] A quantum dot light-emitting diode, which differs from Example 1 in that the electron transport layer is made of only ZnO.

[0098] Example 2:

[0099] A quantum dot light-emitting diode, the fabrication method of which includes:

[0100] An anode is fabricated on a substrate, a hole injection layer is fabricated on the anode, a hole transport layer is fabricated on the hole injection layer, a quantum dot emitting layer is fabricated on the hole transport layer, an electron transport layer is fabricated on the quantum dot emitting layer, and a cathode is fabricated on the electron transport layer. After the device fabrication is completed, the device is heat-treated at 120°C for 50 min. The substrate is a glass substrate; the bottom electrode is ITO with a thickness of 80 nm; the hole injection layer is PEDOT:PSS with a thickness of 40 nm; the hole transport layer is TFB with a thickness of 100 nm; the quantum dot emitting layer is CdZnSe / ZnSeS / ZnS, each with a thickness of 70 nm; the electron transport layer is a mixed layer of ZnO and MOFs materials, in which the MOFs material is MOF-801, which adsorbs gases such as H2O, O2, and CO2 in the following proportions. The molar ratio of H2O to CO2 is 1:1, the molar ratio of H2O to electron transport material is 0.03:1, the molar ratio of O2 to cathode is 0.04:1, the thickness of electron transport layer is 50 nm, and the top electrode is Al with a thickness of 40 nm.

[0101] Comparative Example 2

[0102] A quantum dot light-emitting diode, which differs from Example 2 in that the electron transport layer is made of only ZnO.

[0103] Example 3:

[0104] A quantum dot light-emitting diode, the fabrication method of which includes:

[0105] An anode was fabricated on a substrate, a hole injection layer was fabricated on the anode, a hole transport layer was fabricated on the hole injection layer, a quantum dot emitting layer was fabricated on the hole transport layer, an electron transport layer was fabricated on the quantum dot emitting layer, and a cathode was fabricated on the electron transport layer. After the device fabrication was completed, it was heat-treated at 120°C for 70 minutes. The substrate was a glass substrate; the bottom electrode was ITO with a thickness of 90 nm; the hole injection layer was PEDOT:PSS with a thickness of 50 nm; the hole transport layer was TFB with a thickness of 80 nm. The quantum dot emitting layer was CdZnSe / ZnSe / ZnSeS / ZnS, each with a thickness of 60 nm. The electron transport layer was a mixed layer of ZnO and MOF materials, in which the MOF material was IRMOF-16, which adsorbed gases such as H2O, O2, and CO2 in the following proportions. The molar ratio of H2O to CO2 is 1:1, the molar ratio of H2O to electron transport material is 0.04:1, the molar ratio of O2 to cathode is 0.03:1, the thickness of electron transport layer is 60 nm, and the top electrode is Al with a thickness of 40 nm.

[0106] Comparative Example 3

[0107] A quantum dot light-emitting diode, which differs from Example 3 in that the electron transport layer is made of only ZnO.

[0108] Example 4:

[0109] A quantum dot light-emitting diode, the fabrication method of which includes:

[0110] An anode was fabricated on a substrate, a hole injection layer was fabricated on the anode, a hole transport layer was fabricated on the hole injection layer, a quantum dot emitting layer was fabricated on the hole transport layer, an electron transport layer was fabricated on the quantum dot emitting layer, and a cathode was fabricated on the electron transport layer. After the device fabrication was completed, it was heat-treated at 120°C for 60 minutes. The substrate was a glass substrate; the bottom electrode was ITO with a thickness of 80 nm; the hole injection layer was PEDOT:PSS with a thickness of 40 nm; the hole transport layer was TFB with a thickness of 100 nm. The quantum dot emitting layer was CdZnSe / ZnSe / ZnS, each with a thickness of 70 nm; the electron transport layer was a mixed layer of ZnO and MOFs materials, in which the MOFs material was MFM-520, which adsorbed gases such as H2O, O2, and CO2 in the following proportions. The molar ratio of H2O to CO2 is 1:1, the molar ratio of H2O to electron transport material is 0.01:1, the molar ratio of O2 to cathode is 0.03:1, the thickness of electron transport layer is 60 nm, and the top electrode is Al with a thickness of 50 nm.

[0111] Comparative Example 4

[0112] A quantum dot light-emitting diode, which differs from Example 4 in that the electron transport layer is made of only ZnO.

[0113] Example 5:

[0114] A quantum dot light-emitting diode, the fabrication method of which includes:

[0115] An anode was fabricated on a substrate, a hole injection layer was fabricated on the anode, a hole transport layer was fabricated on the hole injection layer, a quantum dot emitting layer was fabricated on the hole transport layer, an electron transport layer was fabricated on the quantum dot emitting layer, and a cathode was fabricated on the electron transport layer. After the device fabrication was completed, it was heat-treated at 120°C for 60 minutes. The substrate was a glass substrate; the bottom electrode was ITO with a thickness of 80 nm; the hole injection layer was PEDOT:PSS with a thickness of 40 nm; the hole transport layer was TFB with a thickness of 100 nm. The quantum dot emitting layer was CdZnSe / ZnSe / ZnS, each with a thickness of 80 nm; the electron transport layer was a mixed layer of ZnO and MOFs materials, in which the MOFs material was MIL-101, which adsorbed gases such as H2S and CO2 in the following proportions. The molar ratio of H2S to CO2 is 1:1, the molar ratio of H2S to electron transport material is 0.02:1, the thickness of the electron transport layer is 50 nm, and the top electrode is Al with a thickness of 50 nm.

[0116] Comparative Example 5

[0117] A quantum dot light-emitting diode, which differs from Example 5 in that the electron transport layer is made of only ZnO.

[0118] Example 6:

[0119] A quantum dot light-emitting diode, the fabrication method of which includes:

[0120] An anode was fabricated on a substrate, a hole injection layer was fabricated on the anode, a hole transport layer was fabricated on the hole injection layer, a quantum dot emitting layer was fabricated on the hole transport layer, an electron transport layer was fabricated on the quantum dot emitting layer, and a cathode was fabricated on the electron transport layer. After the device fabrication was completed, it was heat-treated at 120°C for 60 min. The substrate was a glass substrate; the bottom electrode was ITO with a thickness of 90 nm; the hole injection layer was PEDOT:PSS with a thickness of 40 nm; the hole transport layer was TFB with a thickness of 100 nm. The quantum dot emitting layer was CdZnSe / ZnSeS / ZnS, each with a thickness of 70 nm. The electron transport layer was a mixed layer of ZnO and MOFs materials, in which the MOFs material was MIL-53(Fe), and gases such as H2S and CO2 were adsorbed in the following ratio: the molar ratio of H2S to CO2 was 1:1, and the molar ratio of H2S to electron transport material was 0.02:1. The electron transport layer is 50 nm thick; the top electrode is Al with a thickness of 60 nm.

[0121] Comparative Example 6

[0122] A quantum dot light-emitting diode, which differs from Example 6 in that the electron transport layer is made of only ZnO.

[0123] Example 7:

[0124] A quantum dot light-emitting diode, the fabrication method of which includes:

[0125] An anode was fabricated on a substrate, a hole injection layer was fabricated on the anode, a hole transport layer was fabricated on the hole injection layer, a quantum dot emitting layer was fabricated on the hole transport layer, an electron transport layer was fabricated on the quantum dot emitting layer, and a cathode was fabricated on the electron transport layer. After the device fabrication was completed, it was heat-treated at 120°C for 60 minutes. The substrate was a glass substrate; the bottom electrode was ITO with a thickness of 80 nm; the hole injection layer was PEDOT:PSS with a thickness of 40 nm; the hole transport layer was TFB with a thickness of 100 nm. The quantum dot emitting layer was CdZnSe / ZnSe / ZnS, each with a thickness of 80 nm. The electron transport layer was a mixed layer of ZnO and MOF materials, in which the MOF material was MIL-101, which adsorbed gases such as HI and CO2 in the following proportions. The molar ratio of HI to CO2 is 1:1, the molar ratio of HI to electron transport material is 0.03:1, the thickness of the electron transport layer is 50 nm, and the top electrode is Al with a thickness of 50 nm.

[0126] Comparative Example 7

[0127] A quantum dot light-emitting diode, which differs from Example 7 in that the electron transport layer is made of only ZnO.

[0128] Example 8:

[0129] An anode was fabricated on a substrate, a hole injection layer was fabricated on the anode, a hole transport layer was fabricated on the hole injection layer, a quantum dot emitting layer was fabricated on the hole transport layer, an electron transport layer was fabricated on the quantum dot emitting layer, and a cathode was fabricated on the electron transport layer. After the device fabrication was completed, it was heat-treated at 120°C for 60 min. The substrate was a glass substrate; the bottom electrode was ITO with a thickness of 90 nm; the hole injection layer was PEDOT:PSS with a thickness of 40 nm; the hole transport layer was TFB with a thickness of 100 nm. The quantum dot emitting layer was CdZnSe / ZnSeS / ZnS, each with a thickness of 70 nm. The electron transport layer was a mixed layer of ZnO and MOFs materials, in which the MOFs material was MIL-53(Fe), which adsorbed gases such as HCN and CO2 in the following proportions. The molar ratio of HCN to CO2 is 1:1, the molar ratio of HCN to electron transport material is 0.03:1, the thickness of the electron transport layer is 50 nm, and the top electrode is Al with a thickness of 60 nm.

[0130] Comparative Example 8

[0131] A quantum dot light-emitting diode, which differs from Example 8 in that the electron transport layer is made of only ZnO.

[0132] The performance of the quantum dot light-emitting diodes prepared in Comparative Examples 1-8 and Examples 1-8 was tested using the following methods:

[0133] (1) External quantum dot efficiency:

[0134] The ratio of electron-hole pairs injected into a quantum dot to emitted photons, expressed as a percentage (%), is an important parameter for evaluating the quality of electroluminescent devices. It can be measured using an EQE optical testing instrument. The specific calculation formula is as follows:

[0135]

[0136] In the formula, ηe is the optical output coupling efficiency, ηγ is the ratio of recombination carriers to injected carriers, χ is the ratio of the number of excitons generating photons to the total number of excitons, and K... R K is the radiation process rate. NR This represents the rate of a non-radiative process.

[0137] Test conditions: Conducted at room temperature with an air humidity of 30-60%.

[0138] (2) QLED device lifetime: The time required for the brightness of a device to decrease to a certain percentage of its maximum brightness under constant current or voltage driving. The time for the brightness to decrease to 95% of the maximum brightness is defined as T95, and this lifetime is the measured lifetime. To shorten the testing cycle, device lifetime testing is usually performed by accelerating device aging under high brightness, referencing OLED device testing, and the lifetime under high brightness is obtained by fitting the extended exponential decay brightness decay fitting formula. For example, the lifetime at 1000 nits is T95 = 1000 nits. The specific calculation formula is as follows:

[0139]

[0140] T95 in the formula L For longer lifespan at low brightness, T95 H For the measured lifetime under high brightness, L H To accelerate the device to its maximum brightness, L L The value is 1000 nits, and A is the acceleration factor. For OLEDs, this value is usually 1.6 to 2. In this experiment, the lifetime of several groups of green QLED devices under rated brightness was measured, and the value of A was found to be 1.7.

[0141] The life test system was used to test the life of the corresponding devices. The test conditions were: room temperature and air humidity of 30-60%.

[0142] The test results are shown in Table 1 below.

[0143] Table 1

[0144]

[0145]

[0146] As can be seen from the table above, the luminous efficiency and lifespan of the quantum dot light-emitting diode provided in this application embodiment are significantly higher than those of the comparative example. This may be attributed to the use of a material storage material to contain an active substance that can react to generate carbonic acid. The generated carbonic acid can react with the electron transport material to form a metal carbonate that is uniformly dispersed in the electron transport layer, thereby improving the luminous efficiency and lifespan of the quantum dot light-emitting diode.

[0147] The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A light-emitting diode, characterized in that, The system includes an electron transport layer, the materials of which include an electron transport material, a matter storage material, and a metal carbonate. The electron transport material contains a metal element, and the matter storage material has a porous structure. The electron transport material contains a metal element, the substance storage material has a porous structure, and the metal carbonate is obtained by reacting an active substance contained in the substance storage material with the electron transport material. The active substance includes at least CO2.

2. The light-emitting diode as described in claim 1, characterized in that, The active substances also include H2O and O2, wherein the molar ratio of H2O to CO2 is 0.8~2:

1. The molar ratio of H2O to the electron transport material is 0.01 to 1:

1.

3. The light-emitting diode as described in claim 2, characterized in that, The molar ratio of H2O to CO2 is 1:

1.

4. The light-emitting diode as described in claim 1, characterized in that, The storage material contains an inorganic acid, and the molar ratio of the inorganic acid to the CO2 is 0.8~2:

1. The molar ratio of the inorganic acid to the electron transport material is 0.01 to 1:

1. The inorganic acids are selected from dichromic acid, diphosphoric acid, hypoiodic acid, hypochlorous acid, hypobromic acid, hypophosphoric acid, hyposulfuric acid, superoxide acid, iodic acid, telluric acid, fluoroboric acid, fluorosilicic acid, fluoroantimonyic acid, fluorophosphoric acid, fluorosulfuric acid, fluoroplatinic acid, fluorooxynic acid, vanadic acid, perchloric acid, permanganic acid, ferric acid, periodic acid, perbromic acid, perxenic acid, chromic acid, silicic acid, cobalt acid, peroxymonosulfuric acid, persulfuric acid, perdisulfuric acid, percarboxylic acid, perboric acid, percarbonic acid, peroxyacid, pyrophosphate, pyrosulfuric acid, metabisulfite, tetrathionine, dithionite, phosphoric acid, phosphomolybdic acid, thiosulfate, sulfuric acid, thiocyanate, chloric acid, chloroauric acid, chloroplatinic acid, and chlorosulfonic acid. Aluminic acid, manganese acid, molybdic acid, nickel acid, boric acid, metaboric acid, metaphosphoric acid, metaarsenic acid, metaaluminic acid, lead acid, cyanic acid, hydroiodic acid, hydroazide acid, hydrotelluric acid, hydrofluoric acid, hydrosulfuric acid, hydrochloric acid, hydrocyanic acid, hydrobromic acid, arsenic acid, trisilicic acid, tetraboric acid, tetrahydroxyaluminic acid, tetrahydroxycopperic acid, titanic acid, carbonic acid, ferric acid, tungstic acid, nitric acid, selenic acid, stannic acid, zincic acid, bromic acid, xenonic acid, telluric acid, sulfurous acid, phosphoric acid, chloric acid, hydrochloric acid, chromic acid, leadous acid, arsenic acid, nitrous acid, selenite, stannic acid, uranic acid, orthosilicic acid, orthophosphoric acid, orthosulfuric acid, orthocarbonic acid, orthocarbonic acid.

5. The light-emitting diode as described in claim 4, characterized in that, The molar ratio of the inorganic acid to the CO2 is 1:

1.

6. The light-emitting diode as described in any one of claims 1 to 5, characterized in that, The material storage material is selected from at least one of MOFs and COFs materials.

7. The light-emitting diode as described in any one of claims 1 to 5, characterized in that, The content ratio of the electron transport material to the material storage material is 0.01~0.5:

1. The electron transport material is selected from doped or undoped metal compounds and non-metal compounds doped with metal elements. In the non-metallic compounds and doped metallic compounds, the doping elements are each independently selected from at least one of Al, Mg, In, Li, Ga, Cd, Cs, and Cu.

8. The light-emitting diode as described in any one of claims 1 to 5, characterized in that, The content ratio of the electron transport material to the material storage material is 0.01~0.5:

1. The electron transport material is selected from at least one of doped or undoped metal oxides and doped or undoped semiconductor materials. The metal oxide is selected from titanium dioxide, zinc oxide, zirconium oxide, tin oxide, tungsten oxide, tantalum oxide, hafnium oxide, aluminum oxide, zirconium silicon oxide, barium titanium oxide, and barium zirconium oxide. The semiconductor material is selected from CdS, ZnSe and ZnS.

9. The light-emitting diode as described in claim 1, characterized in that, The reaction between the active substance and the electron transport material is carried out under vacuum and / or heat treatment.

10. The light-emitting diode as described in claim 9, characterized in that, The vacuum level is less than 0.1 MPa. The heating temperature for the heat treatment is 40℃~180℃, and the heating time is 1min~48h.

11. The light-emitting diode as claimed in claim 1, characterized in that, The light-emitting diode also includes a cathode, which comprises a metal. The material storage material contains O2, and the interface between the cathode and the electron transport layer contains a metal oxide, which is obtained by reacting O2 with a metal in the cathode.

12. A display device, characterized in that, The display device includes a light-emitting diode as described in any one of claims 1-11.

Citation Information

Patent Citations

  • Organic electroluminescent device and manufacturing method thereof

    CN103579508A

  • Organic electroluminescence device and manufacturing method thereof

    CN103682166A